Screw extrusion technology — past, present and future - Sakai, T. (Polimery, 2013)
Extrusion using a screw extruder has been playing very important roles in polymers processing as one of the basic processing technologies for producing compounds and various products such as pipes, car parts, films, etc. In this paper the history and recent technology progress in screw extrusion are reviewed, mainly focused on Japan. Screw extrusion has a long history starting from food processing to rubber and plastics, and is now applied to various fields, such as compounding, fiber spinning, film making, blow molding and injection molding. Recent progress in extrusion technology allows for precise selection of conditions, providing for production of polymers and nanocomposites with required properties, e.g. morphology/structure, as well as significant improvement in production efficiency and energy consumption. Today extrusion technology has been divided into two major streams. The first stream goes towards higher efficiency using larger scale processing lines, and the other towards the production of functional products with special properties, such as nanocomposites and/or polymer blends with specified nanoscale morphology. Starting from the wide range of extrusion technologies against the historical background, this review will cover new advancing extrusion technologies in processing of sustainable/eco- -friendly biopolymers such as PLA or nanocomposites.